2016
DOI: 10.1590/1678-4685-gmb-2016-0032
|View full text |Cite
|
Sign up to set email alerts
|

The effects of old and recent migration waves in the distribution of HBB*S globin gene haplotypes

Abstract: Sickle cell hemoglobin is the result of a mutation at the sixth amino acid position of the beta (β) globin chain. The HBB*S gene is in linkage disequilibrium with five main haplotypes in the β-globin-like gene cluster named according to their ethnic and geographic origins: Bantu (CAR), Benin (BEN), Senegal (SEN), Cameroon (CAM) and Arabian-Indian (ARAB). These haplotypes demonstrated that the sickle cell mutation arose independently at least five times in human history. The distribution of βS haplotypes among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 57 publications
1
10
0
2
Order By: Relevance
“…The gene frequency is highest in West African countries with 1 in 4 to 3 (25–30%) being carriers of HbS compared to 1/400 African Americans and is variable in European populations [ 14 , 15 , 16 ]. The prevalence of SCD in developed countries is increasing partly due to migration from high prevalent countries [ 17 , 18 , 19 , 20 ]. It is estimated that over 14,000 people live with SCD in the UK, similar to France, while countries like Italy, Germany have seen increasing numbers from Africa [ 21 , 22 , 23 , 24 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…The gene frequency is highest in West African countries with 1 in 4 to 3 (25–30%) being carriers of HbS compared to 1/400 African Americans and is variable in European populations [ 14 , 15 , 16 ]. The prevalence of SCD in developed countries is increasing partly due to migration from high prevalent countries [ 17 , 18 , 19 , 20 ]. It is estimated that over 14,000 people live with SCD in the UK, similar to France, while countries like Italy, Germany have seen increasing numbers from Africa [ 21 , 22 , 23 , 24 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Rather than using genotyping individually, the haplotype analysis identifies common genetic features in a population [ 10 ]. Apart from this, several previous studies have shown that HBB haplotype analysis provides crucial information on genetic variations and haplotypes of different populations [ 20 - 22 ]. A study by Zhang et al., on genetic heterogeneity of HBB in various geographic populations of Yunnan in Southwestern China, identified seven different HBB haplotypes among 41 β-thalassemic chromosomes, where haplotype I and haplotype V were more than 65% (28 β-thalassemic chromosomes), while the remaining percentages were distributed to the other haplotypes [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, even with the severe form of the disease, SCA patients have a life expectancy in the UK of 67 years, with 94% childhood survival rates for uncomplicated SCD (Quinn et al, 2010;Gardner et al, 2016). Migration has distributed SCD worldwide, highlighting healthcare inequalities, where the transition from acute to chronic settings remains limited to high-income countries (Piel et al, 2013b;Lindenau et al, 2016).…”
Section: Incidence Burden and Screeningmentioning
confidence: 99%